The SG6043 airfoil optimization for low Reynolds number applications in wind turbines - Davari, Hossein Seifi; Jamalabadi, Mohammad Yaghoub Abdollahzadeh; Davari, Mohsen Seify (Mechanical Engineering Advances, 2025)
This study focuses on optimizing the SG6043 airfoil for small wind turbines (SWTs) operating at low Reynolds numbers (Re = 100,000 to 600,000). Using XFOIL software, 71 airfoils were analyzed, and the SG6043 airfoil demonstrated the highest lift-to-drag ratio (CL/CD). Three modified airfoils were designed by varying the thickness-to-camber ratio (t/c) between 0.5 and 1.5. The SG6043 modified 1 airfoil achieved a maximum CL/CD of 184.85 at Re = 600,000, outperforming other airfoils. These findings provide valuable insights for designing more efficient SWTs for low wind speed applications. At first, 71 airfoils, including some symmetrical National Advisory Committee for Aeronautics (NACA) 4-digit, NACA 5-digit, Eppler series, Selig series, and other airfoils with higher aerodynamic performance at Reynolds numbers (Re) of 100,000 to 600,000 (the operation range for small wind turbines, SWTs), were chosen and analyzed in XFOIL software to determine their lift-to-drag ratio (CL/CD). The results showed that the SG6043 airfoil had the highest maximum CL/CD when compared to the other airfoils. To investigate and enhance the shape modification of the airfoil utilizing variations in thickness-to-camber ratio (t/c) and to determine the ideal t/c at Re of 100,000 to 600,000, the SG6043 airfoil was used. Based on the findings, 0.5 to 1.5 was the optimum t/c at Re of 100,000 to 600,000 for the development of the SG6043 airfoil, which had the maximum CL/CD. Then, three airfoils with varying thicknesses and cambers were designed and analyzed at the mentioned Re, with the optimal t/c being between 0.5 and 1.5. The findings indicated that when the Re increased, the SG6043 modified airfoil’s aerodynamic efficiency enhanced. SG6043 modified 1 airfoil presented the greatest CL/CD of 184.85 at a Re of 600,000. For the SG6043 modified 2 airfoil, the maximum stall angle (AoAstall) of 13° was demonstrated for Re of 300,000 to 600,000. Maximum CL/CD values for SG6043 modified 1, SG6043 modified 3, and SG6043 modified 2 were 184.85, 182.36, and 177.25, respectively. SG6043 modified 2, SG6043 modified 1, and SG6043 modified 3 had peak lift coefficients (CL) of 1.798, 1.79, and 1.788, respectively. SG6043 modified airfoils performed well in the drag bucket when initial lift increases were accompanied by either steady or decreasing drag.